Resíduos sólidos urbanos como tema ambiental: reflexões a partir de um curso de educação ambiental semipresencial para professores do ensino básico - Canedo, Patricia Lemiszka Ribas (2014)
When facing the severe problems caused by Urban Solid Waste (USW), Environmental Education (EE) is one of the strategies for tackling this issue as well as other aspects of the environmental crisis. In formal education, the role of the teachers is extremely important so that EE worked in a continuous, critical and interdisciplinary way. The present paper reports and discusses the presentation of an extension course in EE to 86 teachers of public basic schools of the state of Paraná, using as environmental theme the USW. The course developed in the semi-distance modality using Virtual Learning Environment (VLE) Moodle 2.5 platform Federal Technological University of Paraná.The methodological approach used in this research was the collaborative research-action. In person meetings theoretical issues and proposals for pedagogical practice worked. In the virtual environment, there was discussion and workshops for action proposals where the data for this research through semi- structured questionnaires, data collected in the AVA (forums, tasks, and collaborative activities) collected. Data analyzed through a quali-quantitative approach. This research showed most teachers did not have enough knowledge about USW and rarely employ EE themes within their educational practices. The several activities conducted throughout the course led to important reflections on environmental issues, mainly the ones related to USW generation and management. We consider continuous formation courses to be one of the alternatives to reduce the gaps present in the formation of teachers and to serve as potentializers for the development of EE in schools.